Superoxide Dismutases in Pancreatic Cancer - Justin G. Wilkes; Matthew S. Alexander; Joseph J. Cullen (Antioxidants, 2017)
The incidence of pancreatic cancer is increasing as the population ages but treatment advancements continue to lag far behind. The majority of pancreatic cancer patients have a K-ras oncogene mutation causing a shift in the redox state of the cell, favoring malignant proliferation. This mutation is believed to lead to nicotinamide adenine dinucleotide phosphate (NADPH) oxidase activation and superoxide overproduction, generating tumorigenic behavior. Superoxide dismutases (SODs) have been studied for their ability to manage the oxidative state of the cell by dismuting superoxide and inhibiting signals for pancreatic cancer growth. In particular, manganese superoxide dismutase has clearly shown importance in cell cycle regulation and has been found to be abnormally low in pancreatic cancer cells as well as the surrounding stromal tissue. Likewise, extracellular superoxide dismutase expression seems to favor suppression of pancreatic cancer growth. With an increased understanding of the redox behavior of pancreatic cancer and key regulators, new treatments are being developed with specific targets in mind. This review summarizes what is known about superoxide dismutases in pancreatic cancer and the most current treatment strategies to be advanced from this knowledge.